Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Get expert answers to your questions quickly and accurately from our dedicated community of professionals. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

If [tex][tex]$f(x)=2x$[/tex][/tex] and [tex][tex]$g(x)=x^3$[/tex][/tex], what is [tex][tex]$(f \circ g)(-3)$[/tex][/tex]?

A. -6
B. -27
C. 54
D. -54


Sagot :

To solve the problem and find [tex]\((f \circ g)(-3)\)[/tex], let's break it down step by step.

Firstly, let's understand what [tex]\((f \circ g)(x)\)[/tex] means. This notation is read as "f of g of x," which means we need to first apply the function [tex]\(g(x)\)[/tex] and then apply the function [tex]\(f\)[/tex] to the result obtained from [tex]\(g(x)\)[/tex].

We have the functions:
[tex]\[ g(x) = x^3 \][/tex]
[tex]\[ f(x) = 2x \][/tex]

Step 1: Evaluate [tex]\(g(-3)\)[/tex]
[tex]\[ g(-3) = (-3)^3 = -27 \][/tex]

Step 2: Use the result from Step 1 as the input for the function [tex]\(f\)[/tex]:
[tex]\[ f(g(-3)) = f(-27) \][/tex]

Step 3: Evaluate [tex]\(f(-27)\)[/tex]
[tex]\[ f(-27) = 2 \times -27 = -54 \][/tex]

Therefore, [tex]\((f \circ g)(-3) = -54\)[/tex].

The correct answer is:
D. -54